Effect of Hydroxypropyl Methylcellulose Concentration Variations as a Gelling Agent on the Physical Quality of Hydrogel Formulations Containing Ethanol Extract of Impatiens balsamina L. Herb - Buana, Komang Dirga Mega; Pebriani, Ni Luh Gede Wiwin; Suryani, Ade Irma; Mendra, Ni Nyoman Yudianti; Candraningrat, I Dewa Agung Ayu Diva; Sasadara, Maria Malida Vernandes (Indonesian Journal of Medicine, 2025)
Background: Impatiens balsamina L. herb is known to possess anti-inflammatory and antioxidant activities, making it a promising candidate for development as an active ingredient in topical formulations. Hydrogels are considered an ideal delivery system for topical wound treatment due to their ability to provide controlled drug release, with hydroxypropyl methylcellulose (HPMC) commonly employed as a stable gelling agent. This study aimed to evaluate the effect of varying HPMC concentrations on the physical quality of hydrogel formulations containing ethanol extract of Impatiens balsamina L. herb. Subjects and Method: This was an experimental study. Hydrogel formulations were prepared with varying concentrations of hydroxypropyl methylcellulose (HPMC) at 1%, 2%, and 3% as the gelling agent. Each formulation was evaluated for physical quality parameters, including organoleptic properties, homogeneity, spreadability, adhesiveness, and pH value, following standard topical formulation testing procedures. Results: The evaluation results showed that all formulations exhibited good homogeneity and pH values within the safe range for skin application. Increasing HPMC concentration did not visually affect the color of the formulations; however, it influenced the formulation consistency, decreased spreadability, and increased adhesiveness. Conclusion: Variations in HPMC concentration in hydrogel formulations containing ethanol extract of Impatiens balsamina L. herb significantly affected the physical quality parameters, particularly consistency, spreadability, and adhesiveness. The formulation with 2% HPMC concentration demonstrated the most optimal physical characteristics for topical application.